Perbandingan Kejadian Retensi Urin antara Persalinan dengan Vakum Ekstraksi dan Persalinan Normal - Nurul Hikmah Petrana; Ova Emilia; Heru Pradjatmo (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Urinary retention after vaginal delivery is a common problem with incidence 1.7% - 17.9%. Assissted vaginal delivery is one risk factor for the occurence of urinary retention.Objective: to compare urinary retention between normal vaginal delivery and assissted vaginal delivery using extraction vacum, and evaluate factors related to urinary retention.Method: The study was prospective cohort design, conducted in 3 hospitals and 2 primary health centres during 6 month period since September 2013- February 2014. Subjects were divided into two groups i.e. normal delivery and assissted delivery using extraction vacum, each 118 subjects. Events of urinary retention was assessed and also related factors were identified. Analysis used Chi-Square test, Fisher test and also logistic regression analysis.Result and Discussion: In total 236 subjects were involved, there was no difference in age and parity among the subjects. Incidence of urinary retention among extraction vacum delivery group was higher (32.2%) compare to normal delivery (11.9%). Multivariate analysis using logistic regression showed that extraction vacum (p=0.074; OR 2.71; 95% CI 1.55-4.73), baby weight (p= 0.230; OR 1.95; 95% CI 0.655.84) and perineal injury (p= 0.614; OR 1.35; 95% CI 0.41-4.36) were not significant risk factors for urinary retention. Length of labour (p=0.003; OR 3.71; 95% CI 1.55-8.86) and parity (p= 0.023; OR 2.29; 95% CI 1.2-4.66) were significant risk factors for urinary retention.Conclusion: Urinary retention is higher among vaginal delivery with extraction vacum compare to normal delivery. Length of labour and parity are external factors related to urinary retention.Keywords: Assissted vaginal delivery, extraction vacum, normal delivery, urinary retention, postpartum